Primary Reconstruction of Total Maxillectomy with Custom-Made Subperiosteal Implant and Temporal Muscle Flap: A Case Report - Giacomo De Riu; Damiano Soma; Andrea Biglio; Maria Teresa Raho; Danilo Mura; Fabio Michelon; Giovanni Salzano; Pasquale Piombino; Jérome R. Lechien; Luigi Angelo Vaira (Applied Sciences, 2023)
Recent reports on secondary restorations with subperiosteal implants have demonstrated promising results in terms of esthetic and functional restoration. We report the case of a reconstruction of a total maxillectomy with a custom-made subperiosteal implant associated with a temporal muscle flap in a patient who could not undergo bone reconstruction with a free flap. This technique made it possible to restore the division between the oral cavity and the mouth, providing a solid anchorage to the dental prosthesis and correcting an oroantral communication with a small palatal obturator. The subperiosteal implant also granted proper soft tissue support in the middle-third of the face. Subperiosteal implants can be safe and effective even in primary maxillary reconstructions for patients who cannot undergo free bone flap reconstructions. In these difficult cases, this type of implant can provide support to the soft tissues of the middle-third of the face and a solid anchorage for dental prostheses or palatal obturators, thus improving the quality of life for patients.